Use of IoT Sensors to Build an Intelligent Monitoring and Control System for Poultry House Environment - Chang, Yuh-Shihng; Tu, Li-Yuan (Sensors and materials, 2023)
In this study, we used an indoor poultry house as the research subject to establish an intelligent monitoring and control system. Because avian influenza spreads through air and seriously affects the growth environment of poultry houses, large outdoor poultry houses in Taiwan have been converted into indoor farms. Considering the health of poultry, through IoT sensors, managers can monitor the environmental status of poultry houses in real time, control environmental data to improve production efficiency and save electricity, and achieve sustainable environmental benefits. The functions of an intelligent monitoring and control system used in this study include the following. (1) The visual interface enables managers to view environmental data and health status easily. (2) Through integration with IoT sensors, the system transmits the data of environmental sensors, such as temperature, humidity, wind speed, light intensity, and CO2 concentration, to a cloud database for subsequent data analysis. (3) The system automatically adjusts power control in accordance with environmental variables to reduce energy consumption. (4) The system records the cumulative usage time of electronic equipment and can estimate power consumption and carbon emission. (5) The user can connect to the background web through a mobile device and realize the control of intelligent monitoring and power analysis to save energy usage. The results of this study have been applied to intelligent poultry houses and are suitable for application to smart farms.